2023
DOI: 10.1155/2023/6082635
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis Identified Glycosyltransferase Signature to Predict Glioma Prognosis and TAM Phenotype

Abstract: Glycosylation is the most common posttranslational modification of proteins. Glycosyltransferase gene differential expression dictates the glycosylation model and is epigenetically regulating glioma progression and immunity. This study is aimed at identifying the glycosyltransferase gene signature to predict the prognosis and immune characteristics of glioma. The glycosyltransferase gene signature of glioma was identified in the TCGA database and validated in the CGGA database. Glioma patients were then divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
(36 reference statements)
2
0
0
Order By: Relevance
“…Our data showed that immune infiltration macrophages were significantly highly expressed in subtypes with high TNF scores. This result is consistent with previous results, which indicate that immune infiltrating macrophages are associated with a high risk of disease and poor overall survival ( 41 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our data showed that immune infiltration macrophages were significantly highly expressed in subtypes with high TNF scores. This result is consistent with previous results, which indicate that immune infiltrating macrophages are associated with a high risk of disease and poor overall survival ( 41 ).…”
Section: Discussionsupporting
confidence: 94%
“…Our data showed that immune infiltration macrophages were significantly highly expressed in subtypes with high TNF scores. This result is consistent with previous results, which indicate that immune infiltrating macrophages are associated with a high risk of disease and poor overall survival (41). Our data showed that immune exhaustion-related PDCD1, CTLA4, and LAG3 are significantly highly expressed in subtypes with high TNF scores, that PD-L1 and PD-L2 can inhibit the activation and cytotoxic effects by binding to PD-1 and that CD80 and CD86 bind to CTLA4 and inhibit the T cell costimulatory signaling pathway.…”
Section: Discussionsupporting
confidence: 94%